ANALYSIS OF ENGLISH SPEAKING ABILITY OF TEN GRADE AT MAN 1 BAUBAU - Maneba, Sanaria; Amiruddin, Esa Penilta; Hernita, WD. (English Education Journal, 2024)
The problem of statement in this research was what are the factors that influence English students speaking ability at the ten grade of Man 1 Baubau. Objective of this research was to find out factors that influence English students speaking ability at the ten grade of Man 1 Baubau. This researcher used qualitative descriptive method. Subject of this researcher was one English teacher and four students of class X 2. This researcher instrument was obsevation, interview and documentation. The results of this researcher indicated the factors that influence English students speaking ability at the ten grade of Man 1 Baubau were: 1) internal factors such as low vocabulary mastery, low grammar understanding, low self confidence, shame and nervousness; 2) external factors such as school environment.